Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Associations between exposure to metals, chlorinated pesticides, and PCBs and differential leukocyte profiles in Flemish adolescents - Fen Zhang; Lützen Portengen; Hamid Y. Hassen; Laura Rodriguez Martin; Madeline Carsique; Amélie Crépet; Jasper Engel; Jacob Van Klaveren; Nicolas Van Larebeke; Willy Baeyens; Stefaan De Henauw; Tim S. Nawrot; et al. (Environmental Research, 2026)

Colonoscopy findings in CDH1 carriers from a multicenter international study - Arjun Chatterjee; Robert Hüneburg; Qijun Yang; Shannon Morrison; Anna Bettzüge; Tim Marwitz; Stefan Aretz; Isabel Spier; Tim Ripperger; Silke Redler; Mykyta Kachanov; Alexander E. Volk; et al. (Familial Cancer, 2025)
Germline (likely-)pathogenic variants (PV) in CDH1 predispose carriers to hereditary diffuse gastric cancer and lobular breast cancer. Previous studies from the United States suggest CDH1 variant carriers have an increased risk for adenomas or sessile serrated lesions (SSL), yet data linking CDH1 PVs and colorectal neoplasia are scarce. We aimed to investigate colonoscopy findings in CDH1 PVs. Adults carrying a PV/LPV in CDH1 with ≥ 1 colonoscopy between 01/01/2004–12/31/2023 were included. Patients were sourced from the David G. Jagelman Inherited Colorectal Cancer Registries at Cleveland Clinic and the German Consortium for Familial Intestinal Cancer. 103 CDH1 PV carriers were included. Most were female (66%) and white (93.1%). The median age at first colonoscopy was 47 years. The adenoma detection rate (ADR) was 29.4% (95% CI:19.9–41.1%) in the German cohort and 48.6% (95% CI: 33.0-64.4%) in the Cleveland cohort ( p = 0.055) and significantly correlated with age (< 45 years, 13.6% (95% CI: 6.40–26.7%); 45–49 years, 52.4% (95% CI: 32.4–71.7%); ≥50 years, 52.6% (95% CI: 37.3–67.5%); p < 0.001). The ADR in Cleveland was higher than the U.S. average ADR but the difference was not statistically significant (48.6% vs. 35.6%, p = 0.08), and the ADR in the German cohort (29.4%) was similar to the national German average risk screening cohort (31.3% in men, p = 0.84; 20.1% in women, p = 0.08). In our screening cohort with CDH1 PV carriers, we demonstrated an ADR of 13.5% in individuals under 45 years, similar to the ADR in patients aged 25–40 years with a family history of CRC. Overall, SSL detection rate was 9.7%. Colorectal cancer was diagnosed in 3 patients (3.2%), 2/3 with an early age of onset before the age of 50 years. This first international study provides preliminary evidence of a higher ADR in U.S. CDH1 PV carriers compared to the general population, with a high number of adenomas detected before the age of 50. This may indicate an increased CRC risk that should be explored in larger studies.

Differences in bed elevation shape subtidal mussel bed stability under high‐energy hydrodynamic events - Zhiyuan Zhao; Jaco C. de Smit; Jacob J. Capelle; Tim Grandjean; Mingxuan Wu; Theo Gerkema; Johan van de Koppel; Tjeerd J. Bouma (Limnology and Oceanography, 2025)
Escalating high‐energy hydrodynamic events, like storms, represent a significant manifestation of global climate change, causing detrimental impacts on various ecosystems and potentially triggering thresholds that result in abrupt shifts in ecosystem states. Despite the potential of such thresholds, few studies have explicitly addressed them. This gap is particularly notable for subtidal ecosystems due to technological challenges in detecting responses of organisms enduring constant submersion. This study focused on subtidal soft‐bottom mussel beds through the development of Biophys loggers for in situ monitoring of the fine‐scale behavior of mussel clusters under hydrodynamic disturbances and a statistical model based on an 11‐yr dataset to perform regional‐scale assessments of mussel bed stability. Multisite monitoring in the Dutch Wadden Sea revealed spatial heterogeneity in mussel bed mobility threshold (i.e., near‐bed orbital velocity inducing mussel movement), with predictable patterns along elevation gradients. Stability assessment in this region demonstrated that mussel beds in shallower areas (i.e., at higher bed elevations) exhibited higher stability than those in deeper areas, a difference that was attributed to the longer return interval of the mobility thresholds in shallow regions. These findings suggest that conditions such as bed elevation can modulate the stress tolerance of mussels and thereby influence the stability of subtidal soft‐bottom mussel beds. This study provides an approach for assessing mussel bed stability, which can also be extended to other comparable ecosystems, such as oyster reefs, to address their stability under climate change, thereby informing strategic management.

Navigating trade-offs in design for sustainability and circularity: A tool for decision making leveraging narratives and multiple criteria decision analysis - Giácomo Parolin; Jacob Arnbjerg; Tim C. McAloone; Daniela C.A. Pigosso (Journal of Cleaner Production, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Enabling environmental sustainability and circularity assessment in technology development: The Value-Impact Scanner - Giácomo Parolin; Jacob Arnbjerg; Henriette A. Eriksen; Tim C. McAloone; Daniela C.A. Pigosso (Sustainable Production and Consumption, 2024)

Honey bee drones are synchronously hyperactive inside the nest - Louisa C. Neubauer; Jacob D. Davidson; Benjamin Wild; David M. Dormagen; Tim Landgraf; Iain D. Couzin; Michael L. Smith (Animal Behaviour, 2023)

Multimodal 3D Mouse Brain Atlas Framework with the Skull-Derived Coordinate System - Johanna Perens; Casper Gravesen Salinas; Urmas Roostalu; Jacob Lercke Skytte; Carsten Gundlach; Jacob Hecksher-Sørensen; Anders Bjorholm Dahl; Tim B. Dyrby (Neuroinformatics, 2023)

Attributes of climate resilience in fisheries: From theory to practice - Julia G. Mason; Jacob G. Eurich; Jacqueline D. Lau; Willow Battista; Christopher M. Free; Katherine E. Mills; Kanae Tokunaga; Lily Z. Zhao; Mark Dickey‐Collas; Mireia Valle; Gretta T. Pecl; Joshua E. Cinner; et al. (Fish and Fisheries, 2022)
In a changing climate, there is an imperative to build coupled social‐ecological systems—including fisheries—that can withstand or adapt to climate stressors. Although resilience theory identifies system attributes that supposedly confer resilience, these attributes have rarely been clearly defined, mechanistically explained, nor tested and applied to inform fisheries governance. Here, we develop and apply a comprehensive resilience framework to examine fishery systems across (a) ecological, (b) socio‐economic and (c) governance dimensions using five resilience domains: assets, flexibility, organization, learning and agency. We distil and define 38 attributes that confer climate resilience from a coupled literature‐ and expert‐driven approach, describe how they apply to fisheries and provide illustrative examples of resilience attributes in action. Our synthesis highlights that the directionality and mechanism of these attributes depend on the specific context, capacities, and scale of the focal fishery system and associated stressors, and we find evidence of interdependencies among attributes. Overall, however, we find few studies that test resilience attributes in fisheries across all parts of the system, with most examples focussing on the ecological dimension. As such, meaningful quantification of the attributes’ contributions to resilience remains a challenge. Our synthesis and holistic framework represent a starting point for critical application of resilience concepts to fisheries social‐ecological systems.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Seabird Migration Strategies: Flight Budgets, Diel Activity Patterns, and Lunar Influence - Anne-Sophie Bonnet-Lebrun; Maria P. Dias; Richard A. Phillips; José P. Granadeiro; M. de L. Brooke; Olivier Chastel; Thomas A. Clay; Annette L. Fayet; Olivier Gilg; Jacob González-Solís; Tim Guilford; Sveinn A. Hanssen; et al. (Frontiers in Marine Science, 2021)
Every year, billions of birds undertake extensive migrations between breeding and non-breeding areas, facing challenges that require behavioural adjustments, particularly to flight timing and duration. Such adjustments in daily activity patterns and the influence of extrinsic factors (e.g., environmental conditions, moonlight) have received much more research attention in terrestrial than marine migrants. Taking advantage of the widespread deployment in recent decades of combined light-level geolocator-immersion loggers, we investigated diel organisation and influence of the moon on flight activities during the non-breeding season of 21 migrant seabird species from a wide taxonomic range (6 families, 3 orders). Migrant seabirds regularly stopped (to either feed or rest) during migration, unlike some terrestrial and wetland birds which fly non-stop. We found an overall increase for most seabird species in time in flight and, for several species, also in flight bout duration, during migration compared to when resident at the non-breeding grounds. Additionally, several nocturnal species spent more of the day in flight during migration than at non-breeding areas, and vice versa for diurnal species. Nocturnal time in flight tended to increase during full moon, both during migration and at the non-breeding grounds, depending on species. Our study provides an extensive overview of activity patterns of migrant seabirds, paving the way for further research on the underlying mechanisms and drivers.

An Optimized Mouse Brain Atlas for Automated Mapping and Quantification of Neuronal Activity Using iDISCO+ and Light Sheet Fluorescence Microscopy - Johanna Perens; Casper Gravesen Salinas; Jacob Lercke Skytte; Urmas Roostalu; Anders Bjorholm Dahl; Tim B. Dyrby; Franziska Wichern; Pernille Barkholt; Niels Vrang; Jacob Jelsing; Jacob Hecksher-Sørensen (Neuroinformatics, 2021)
In recent years, the combination of whole-brain immunolabelling, light sheet fluorescence microscopy (LSFM) and subsequent registration of data with a common reference atlas, has enabled 3D visualization and quantification of fluorescent markers or tracers in the adult mouse brain. Today, the common coordinate framework version 3 developed by the Allen’s Institute of Brain Science (AIBS CCFv3), is widely used as the standard brain atlas for registration of LSFM data. However, the AIBS CCFv3 is based on histological processing and imaging modalities different from those used for LSFM imaging and consequently, the data differ in both tissue contrast and morphology. To improve the accuracy and speed by which LSFM-imaged whole-brain data can be registered and quantified, we have created an optimized digital mouse brain atlas based on immunolabelled and solvent-cleared brains. Compared to the AIBS CCFv3 atlas, our atlas resulted in faster and more accurate mapping of neuronal activity as measured by c-Fos expression, especially in the hindbrain. We further demonstrated utility of the LSFM atlas by comparing whole-brain quantitative changes in c-Fos expression following acute administration of semaglutide in lean and diet-induced obese mice. In combination with an improved algorithm for c-Fos detection, the LSFM atlas enables unbiased and computationally efficient characterization of drug effects on whole-brain neuronal activity patterns. In conclusion, we established an optimized reference atlas for more precise mapping of fluorescent markers, including c-Fos, in mouse brains processed for LSFM.

Long‐term development and trajectories of inferred lake‐water organic carbon and pH in naturally acidic boreal lakes - Erik Myrstener; Sofia Ninnes; Carsten Meyer‐Jacob; Tim Mighall; Richard Bindler (Limnology and Oceanography, 2021)
Monitoring of surface waters in the boreal region over the last decades shows that waters are becoming browner. This timeframe may not, however, be sufficient to capture underlying trajectories and driving mechanisms of lake‐water quality, important for prediction of future trajectories. Here we synthesize data from seven lakes in the Swedish boreal landscape, with contemporary lake‐water total organic carbon (TOC) concentrations of 1.4–14.4 mg L −1 , to conceptualize how natural and particularly human‐driven processes at the landscape scale have regulated lake‐water TOC levels over the Holocene. Sediment‐inferred trends in TOC are supported by several proxies, including diatom‐inferred pH. Before ~ 700 ce , all lakes were naturally acidic (pH 4.7–5.4) and the concentrations of inferred lake‐water TOC were high (10–23 mg L −1 ). The introduction of traditional human land use from ~ 700 ce led to a decrease in lake‐water TOC in all lakes (to 5–14 mg L −1 ), and in four poorly buffered lakes, also to an increase in pH by > 1 unit. During the 20 th century, industrial acid deposition was superimposed on centuries of land use, which resulted in unprecedentedly low lake‐water TOC in all lakes (3–11 mg L −1 ) and severely reduced pH in the four poorly buffered lakes. The other lakes resisted pH changes, likely due to close connections to peatlands. Our results indicate that an important part of the recent browning of boreal lakes is a recovery from human impacts. Furthermore, on a conceptual level we stress that contemporary environmental changes occur within the context of past, long‐term disturbances.

The decline of mussel aquaculture in the European Union: causes, economic impacts and opportunities - Lamprakis Avdelas; Edo Avdic‐Mravlje; Ana Cristina Borges Marques; Suzana Cano; Jacob J. Capelle; Natacha Carvalho; Maria Cozzolino; John Dennis; Tim Ellis; José M. Fernández Polanco; Jordi Guillen; Tobias Lasner; et al. (Reviews in Aquaculture, 2021)
In contrast to the increasing aquaculture production of mussels worldwide, production in the European Union (EU) has shown a decreasing trend over the last two decades. Aquaculture production of mussels in the EU peaked in the late 1990s at more than 600 000 tonnes; by 2016, production volume had dropped by 20% to 480 000 tonnes. As mussel production represents more than ⅓ of EU aquaculture production, this decrease is an important contributor to the stagnation of EU aquaculture. Previous studies have suggested diseases, lack of mussel seed (spat), and low profitability as the main causes of the EU mussel production decrease. In this study, we investigate how economic and environmental factors have contributed. Moreover, we examine if the different mussel production techniques (raft, longline, on‐bottom, and ‘bouchot’) have been differently affected, by analysing the economic performance and cost structure evolution for the period 2010–2016. We complement these results with a SWOT (strengths, weaknesses, opportunities, and threats) analysis of the EU mussel sector based on expert knowledge.

Revisiting an arid LGM using fluvial archives: a luminescence chronology for palaeochannels of the Murrumbidgee River, south‐eastern Australia - Daniela Mueller; Zenobia Jacobs; Tim J. Cohen; David M. Price; Ivars V. Reinfelds; James Shulmeister (Journal of Quaternary Science, 2018)
The Riverine Plain in south‐eastern Australia contains numerous palaeochannels that are much larger than the present rivers and provide evidence about past hydrological conditions. Previous research suggested optima in fluvial activity both before and after the peak of the Last Glacial Maximum (LGM; 21 ± 3 ka), and, in some cases, throughout the LGM. In this study, we revisit palaeochannel remnants of the Gum Creek and Yanco palaeochannel systems along the Murrumbidgee River, which drains the high‐elevation catchments of the Australian Alps in south‐eastern Australia. We date fluvial and aeolian sediments using single‐grain optically stimulated luminescence (OSL) and apply thermoluminescence (TL) dating to a subset of samples. We compare the OSL ages to new and previously published TL ages and investigate reasons for age discrepancies between these methods, possible effects of partial bleaching and other factors that may affect luminescence ages. We propose a new OSL‐based chronology for the Gum Creek and Yanco palaeochannel systems and assign periods of enhanced fluvial activity for the Tombullen and Yanco phases to 41–29 and 29–18 ka, respectively. Importantly, we infer that conditions of increased sediment and water discharge persisted for the Murrumbidgee River at the time of the LGM.

DNA hypomethylation in association with internal and external markers of traffic exposure in a panel of healthy adults - Tijs Louwies; Luc Int Panis; Eline Provost; Griet Jacobs; Tim S. Nawrot; Patrick De Boever (Air Quality, Atmosphere & Health, 2018)

Assessing the impact of stocking northern-origin hatchery brook trout on the genetics of wild populations in North Carolina - David C. Kazyak; Jacob Rash; Barbara A. Lubinski; Tim L. King (Conservation Genetics, 2018)

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

De novo mutations in beta-catenin (CTNNB1) appear to be a frequent cause of intellectual disability: expanding the mutational and clinical spectrum - Alma Kuechler; Marjolein H. Willemsen; Beate Albrecht; Carlos A. Bacino; Dennis W. Bartholomew; Hans van Bokhoven; Marie Jose H. van den Boogaard; Nuria Bramswig; Christian Büttner; Kirsten Cremer; Johanna Christina Czeschik; Hartmut Engels; et al. (Human Genetics, 2015)

15 years of processing and dissemination of SPOT-VEGETATION products - Bart Deronde; Walter Debruyn; Eric Gontier; Erwin Goor; Tim Jacobs; Sara Verbeiren; Johan Vereecken (International Journal of Remote Sensing, 2014)

Building local environmental knowledge in undergraduates with experiential wilderness skills and awareness training: the case of environmental sentinels - Jacob C. Brenner; Jason G. Hamilton; Tim Drake; Jed Jordan (Journal of Environmental Studies and Sciences, 2013)

Indigenous culture and adaptation to climate change: sockeye salmon and the St’át’imc people - Colleen Jacob; Tim McDaniels; Scott Hinch (Mitigation and Adaptation Strategies for Global Change, 2010)

Roles of type IV pili, flagellum‐mediated motility and extracellular DNA in the formation of mature multicellular structures in Pseudomonas aeruginosa biofilms - Kim B. Barken; Sünje J. Pamp; Liang Yang; Morten Gjermansen; Jacob J. Bertrand; Mikkel Klausen; Michael Givskov; Cynthia B. Whitchurch; Joanne N. Engel; Tim Tolker‐Nielsen (Environmental Microbiology, 2008)
Summary When grown as a biofilm in laboratory flow chambers Pseudomonas aeruginosa can develop mushroom‐shaped multicellular structures consisting of distinct subpopulations in the cap and stalk portions. We have previously presented evidence that formation of the cap portion of the mushroom‐shaped structures in P. aeruginosa biofilms occurs via bacterial migration and depends on type IV pili ( Mol Microbiol 50: 61–68). In the present study we examine additional factors involved in the formation of this multicellular substructure. While pilA mutants, lacking type IV pili, are deficient in mushroom cap formation, pilH and chpA mutants, which are inactivated in the type IV pili‐linked chemosensory system, showed only minor defects in cap formation. On the contrary, fliM mutants, which are non‐flagellated, and cheY mutants, which are inactivated in the flagellum‐linked chemotaxis system, were largely deficient in cap formation. Experiments involving DNase treatment of developing biofilms provided evidence that extracellular DNA plays a role in cap formation. Moreover, mutants that are deficient in quorum sensing‐controlled DNA release formed microcolonies upon which wild‐type bacteria could not form caps. These results constitute evidence that type IV pili, flagellum‐mediated motility and quorum sensing‐controlled DNA release are involved in the formation of mature multicellular structures in P. aeruginosa biofilms.

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)